Sustainable Supply Chain Management in City Logistics Solutions - I.V. Babenko; A.Yu. Anisimov; V. Yu. Melnikov; I. A. Kubrak; I. I. Golubov; V. L. Boyko (International Journal of Supply Chain Management, 2020)
Abstract-The strategic supply chain processes that influences on the city management. The sustainable logistics and transportation studies constitute a primordial research axis in the enterprises’ governance. The aim of this paper arises on a reflection about the sustainable supply chain management by digitalization and smart technologies. These include product development, customers, manufacturing, vendors, and logistics. The main global introduction of digital technologies in all spheres of human and the state life continues, motivating the creation of new approaches and technological solutions. Public administration through information technologies is currently particularly relevant. The main tool of informatization and digitalization of state and municipal services are the technologies of